2021
DOI: 10.1038/s41582-021-00606-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk–benefit analysis of COVID-19 vaccines — a neurological perspective

Abstract: Rare neurological complications can occur after COVID-19 vaccination, but recent studies show that such complications are much more common after SARS-CoV-2 infection. Novel approaches to risk–benefit analysis such as Bayesian network models can integrate the latest global evidence with local factors to inform decision-making and support the global vaccination effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In phase III clinical trial of the ChAdOx1-nCov-19 vector vaccine, a few cases of transverse myelitis were reported (O'Reilly, 2020; Voysey et al, 2021). Moreover, Serious neurological disorders were reported following different mRNA-based vaccination including transverse myelitis, Guillain-Barré syndrome, cranial nerve neuropathies, myelitis, and facial nerve palsy (García-Grimshaw et al, 2021;Lau & Galea, 2022;Malhotra et al, 2021;Michalik et al, 2022;Wan et al, 2022). A study reviewing case reports and case series reported the occurrence of variable central and peripheral nervous system complications in patients receiving gene-based vaccines including transverse myelitis, Guillain-Barré syndrome, and cerebral venous sinus thrombosis (Sriwastava et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In phase III clinical trial of the ChAdOx1-nCov-19 vector vaccine, a few cases of transverse myelitis were reported (O'Reilly, 2020; Voysey et al, 2021). Moreover, Serious neurological disorders were reported following different mRNA-based vaccination including transverse myelitis, Guillain-Barré syndrome, cranial nerve neuropathies, myelitis, and facial nerve palsy (García-Grimshaw et al, 2021;Lau & Galea, 2022;Malhotra et al, 2021;Michalik et al, 2022;Wan et al, 2022). A study reviewing case reports and case series reported the occurrence of variable central and peripheral nervous system complications in patients receiving gene-based vaccines including transverse myelitis, Guillain-Barré syndrome, and cerebral venous sinus thrombosis (Sriwastava et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…223 Nevertheless, the incidence of anaphylaxis-associated with COVID-19 vaccines is comparable to that of other vaccines 246 and the benefits may outweigh the potential risks of COVID-19 vaccinations. 247,248 Unfortunately, the fear of an allergic reaction has caused vaccine hesitancy in the general public, haltering global vaccination efforts. 249 Polyethylene glycol (PEG) is an additive present in the Pfizer-BioNtech and Moderna mRNA vaccines used to prevent premature degradation of the nanoparticless, 250 and it has been suggested to be the major culprit for anaphylaxis to COVID-19 vaccines.…”
Section: Allergic Reactions To Covid-19 Vaccinesmentioning
confidence: 99%
“…However, the seriousness of VITT from a risk-benefit perspective of COVID-19 vaccines is of relevance 6 . The risk of developing VITT is small (1 case per 26 500 to 127,300 after the first vaccine dose 7 ), while the risk of COVID-19 infection is still highly significant worldwide, having caused millions of deaths and huge morbidity, and social economic damage around the globe.…”
Section: Introductionmentioning
confidence: 99%